2020
DOI: 10.1021/acs.iecr.9b06098
|View full text |Cite
|
Sign up to set email alerts
|

Unusual Ringed/Dendritic Sector Faces in Poly(butylene succinate) Crystallized with Isomeric Polymer

Abstract: Poly­(butylene succinate) (PBSu) and poly­(ethylene adipate) (PEA), isomeric to each other, are mixed in a miscible state, and PBSu crystallized at T c’s where PEA is kept at a molten state. PBSu upon crystallization in the presence of isomeric PEA at various Tc’s develops sector-face spherulitic patterns, which are shown to originate from a common nuclei center. The two faces of sector-face PBSu spherulites are more strikingly contrast when PBSu is highly diluted by isomeric PEA in PBSu/PEA mixtures (PEA = 70… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
7
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

5
2

Authors

Journals

citations
Cited by 8 publications
(7 citation statements)
references
References 40 publications
0
7
0
Order By: Relevance
“…Packing and maturing into multiple (or dual) types of spherulites may be related to nucleation instability, where the initial geometry of nucleus/nuclei (or bundled sheaves) serves as a determining factor for guiding the later lamellae to grow and assemble. In several other polymers, it has been also found that dual or multiple types of spherulites co-exist due to the instability of the initial nucleus, as documented in several literature papers [ 45 , 46 ].…”
Section: Resultsmentioning
confidence: 91%
“…Packing and maturing into multiple (or dual) types of spherulites may be related to nucleation instability, where the initial geometry of nucleus/nuclei (or bundled sheaves) serves as a determining factor for guiding the later lamellae to grow and assemble. In several other polymers, it has been also found that dual or multiple types of spherulites co-exist due to the instability of the initial nucleus, as documented in several literature papers [ 45 , 46 ].…”
Section: Resultsmentioning
confidence: 91%
“…37 Furthermore, the kinetic growth of spherulites is one of the most important factors affecting the final morphology. 38 Common morphologies of crystal aggregates include ringless spherulites, 39 ring-banded spherulites, 40 dendritic spherulites, 41 and many other special morphologies such as feather-like spherulites, 42 seaweed-like spherulites, 37 ring-banded with an eye-like region, 43 dendritic sector-face spherulites, 44 and flower-petal like ring bands, 45 nd so forth. Recently, Wu, et al 46 diluted poly(hydroxybutyrate-cohydroxyvalerate) (with valerate unit = 8−12%) with lowmelting poly(trimethylene adipate), and reported that ringbanded spherulites were observed under a polarized light microscope, with alternate blue/orange-color rings on spherulites.…”
Section: Introductionmentioning
confidence: 99%
“…By adjusting the ratio of the polymers and crystallization temperature, many polymer blends exhibit diverse crystallization morphologies, such as Maltese cross spherulites, ring-banded spherulites, dendritic spherulites, hexagonal spherulites [ 1 ], feather-like spherulites [ 2 ], seaweed spherulites [ 3 ], and the unique Janus-face spherulites [ 4 , 5 ]. However, in recent decades, the formation mechanism of periodic ring-banded spherulites was interpreted controversially.…”
Section: Introductionmentioning
confidence: 99%